Film Pendek PAZIA (Pangan Kaya Zat Besi) sebagai Media Edukasi Pencegahan Anemia pada Remaja Putri: Short Film PAZIA (Iron-Rich Food) as an Educational Media for Anemia Prevention in Teenage Girls - Fadilah, Syahla Anggita; Adiyani, Chika Nabila; Maharani, Ivi Naila Cantik; Natashya, Alfira Nur; Yulistianingsih, Ari; Zuliyanti, Iklima (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Nationally, according to the 2023 Indonesian Health Survey (SKI), the prevalence of anemia was 18.0%. Meanwhile, in Cirebon Regency, the prevalence of anemia reached 30% in adolescent girls. As many as 23% of female students at MA Mafatihul Huda do not understand the importance of consuming iron-rich foods. Therefore, nutrition education is an essential strategy in preventing anemia, but conventional approaches are less attractive to adolescents. This activity aims to assess the effectiveness of the short film media "PAZIA" (Iron-Rich Foods) in increasing the knowledge of adolescent girls about anemia. The methods used included nutritional status assessment, pre-test, film screening, focused group discussion (FGD), and post-test. The subjects of the activity were 21 female students from MA Mafatihul Huda in Cirebon Regency. The results showed that before the intervention, 38.1% of respondents had an underweight nutritional status and 19,1% had irregular menstrual cycles. Following the intervention, there was a 11.4-point increase in the average knowledge scores. Visual-based educational media, in the form of PAZIA film, has proven effective in increasing adolescents' awareness and understanding of the importance of consuming iron-rich foods. Therefore, the use of short films like PAZIA should be expanded in adolescent health education programs.